Entrepreneurial marketing : beyond professional marketing - Kotler, Philip; Kartajaya, Hermawan, 1947-; Hooi, Den Huan (Wiley, 2023)
"Marketing legend Phil Kotler and his colleagues explain why the conventional "professional" approach to marketing is no longer enough. Marketers must be more entrepreneurial, creative, and risk-taking, if they are to adapt to the challenges of the post-pandemic digital world. Entrepreneurial Marketing explains the basics of professional marketing and marketing operations, but also how this foundation must support entrepreneurial thinking and risk-taking. This marriage of professional and entrepreneurship is the new capability marketers need to grow their companies in the next ten years. Each chapter starts with a global or regional case study"--